PREDICTIVE ROLES OF SELF-ESTEEM AND PEER INFLUENCE ON SUBSTANCE ABUSE AMONG SECONDARY SCHOOL STUDENTS - Olubunmi James; Emmanuel Uye; Peter Olapegba (Media Inovasi Pendidikan dan Publikasi, 2026)
Substance abuse has remained a serious concern to the individual, the family, and society. Of particular concern is the involvement of secondary school students in substance abuse. Studies have investigated different predictors of substance abuse with varied results. Therefore, this study examines the predictive roles of self-esteem and peer influence on substance abuse among secondary school students in Lafia Local Government Area (LGA) of Nasarawa State, Nigeria. Cross-sectional survey design was adopted while purposive sampling technique was used to select Lafia LGA. Data were conveniently collected from 414 participants using validated questionnaires and analyzed using multiple regression and independent samples t-test. Two hypotheses were tested and accepted at p <.05 level of significance. The result revealed that self-esteem and peer influence jointly predicted substance abuse among study participants, R2= .037, F (3, 407) = 5.28, p < .05. In addition, self-esteem (ß = .20, p < .05) and peer influence (ß = .19, p < .05) independently predicted substance abuse among study participants. Finally, participants high in peer influence reported significantly higher substance abuse (= 23.67, SD= 12.55) compared to participants with low peer influence (= 19.10, SD = 12.78). The study concludes that self-esteem and peer influence are excellent predictors of substance abuse among study participants. The study recommends that parents should provide an enabling environment for their children to develop positive self-esteem while the school authority and other stakeholders should design and implement programs to educate students on the danger of substance abuse to their life and future career.